Antibiotika-Membranelektrode zur selektiven Erfassung von Ammoniumionenaktivitäten - R.P. Scholer; W. Simon (CHIMIA)
A new liquid-membrane electrode using macrotetrolide antibiotics as ion selective component is described. The electrode shows selectivities of NH4+ over K+ and NH4+ over Na+ of about 10 and over 500 respectively and a linear response to NH4+ in the range 10-1M to 10-5M (slope: 58 mV/log aNH4+ [25°C]).